Assessing The Impact of Digital Media on Disaster Awareness in Secondary School Students - Muhammad Labib Fikron; Yunus Aris Wibowo; Ratih Puspita Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the influence of digital media utilization on students' disaster knowledge at SMP Negeri 1 Grogol, Sukoharjo. This research employed a quantitative correlational design with 283 students selected via stratified random sampling. Data were collected through observation, tests, questionnaires, and documentation, and were analyzed using Spearman's rho correlation to examine the relationship between the two variables. The results showed that students' level of digital media utilization was moderate, while their level of disaster knowledge was high. The correlation test indicated a coefficient of r = 0.155 (p = 0.008), suggesting a positive, significant relationship between digital media use and disaster knowledge, though the relationship was weak. These findings indicate that digital media enhances students' understanding of disasters, yet it is not the sole factor influencing disaster knowledge. Therefore, optimizing the use of digital media in disaster education is necessary to support more effective improvements in students' disaster literacy.